2016
DOI: 10.1177/0309364614556839
|View full text |Cite
|
Sign up to set email alerts
|

Using a three-dimensional model of the Ankle–Foot Orthosis/leg to explore the effects of combinations of axis misalignments

Abstract: Misalignments in the transverse plane had a dominating effect on relative motion between the Ankle-Foot Orthosis and leg emphasizing the importance of including the third dimension in the model and prioritizing accuracy of alignment in the transverse plane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…This finding has also been observed in articulated external fixations of the ankle (Bottlang et al, 1999). In addition, research has shown that misalignment of articulated AFOs with the ankle joint can lead to increases in cuff movement (Fatone and Hansen, 2007;Fatone et al, 2014), which may cause patient discomfort by generating skin and underlying tissue irritation on the shank.…”
Section: Introductionmentioning
confidence: 55%
“…This finding has also been observed in articulated external fixations of the ankle (Bottlang et al, 1999). In addition, research has shown that misalignment of articulated AFOs with the ankle joint can lead to increases in cuff movement (Fatone and Hansen, 2007;Fatone et al, 2014), which may cause patient discomfort by generating skin and underlying tissue irritation on the shank.…”
Section: Introductionmentioning
confidence: 55%
“…The stiffness of the footplate with each of the spacers was evaluated with BRUCE [26]. The height of ADJUST's mechanical hinges could be changed to enable alignment to the anatomical axis of the ankle [37] (Fig. 6i).…”
Section: Appendix Parts Of Adjustmentioning
confidence: 99%
“…12 In this sense, an ideal AFO should be equipped with multiple degrees of freedom (DOFs), and adjustable axial orientations of mechanical joints for the misalignment between axes of the mechanical and anatomical joints may lead to tissue damage and reduced gait efficiency. 13 There are design works on AFOs with multiple DOFs. 6,14,15 However, few of them are equipped with mechanical joints whose axial orientations can be adjusted to align with those of anatomical joints.…”
Section: Introductionmentioning
confidence: 99%